Abrasive wear behavior of EN42 steel used in agricultural discs in field conditions. (December 2022) - Rani, Annu; Singh, T.P.; Singh, Jayant; Patel, Vishal; Kumar Choudhary, Mukesh
Highlights: The wear of agricultural discs used in disc harrow has been analyzed in actual field conditions. Wear pattern of weight loss, radius reduction and thickness reduction have been studied for various makes of discs. The correlations between wear, hardness and time of operation have been developed. Damage morphology of disc was analyzed by observing the microstructure using scanning electron microscope. Abstract: Comprehension wear mechanisms in worn portion is an important area of thermo-mechanical and microstructural research, especially in agricultural knowledge-based applications of abrasive micro-mechanisms of soil engaging tools is scarce. In the current study, wear in different makes (M1, M2, M3, and M4) of EN42 agricultural discs was to see whether there's a difference in weight, radius, thickness, and microstructure with the goal of extending the lifespan. The tests were conducted in a rice-harvested field using a 7 × 7-disc harrow having a speed of 4.5 km/h, soil moisture content was 12–14 % and depth of operation was 10 cm, and duration of operation was 100 h. The cumulative weight, radius, and thickness reduction on M4 make was 547.75 g, 1.78 mm, and 0.55 mm respectively. The make M4 showing minimum wear and maximum working life (3.14 times more than the life of disc M1) was found the best suitable for farm operations followed by M3, M2, and M1.